Metodologia para monitoramento de processos erosivos em margens de reservatórios de usinas hidrelétricas - Dewes, Júnior Joel (2019)
Brazil has experienced in recent decades, an increasing demand of the population and industries by water and energy. This finding combined with the natural abundance of water resources with potential for hydraulic exploitation has intensified the implementation of hydropower plants across the country. However, the implantation of hydropower plants, regardless their size, generates environment changes. One of the impacts generated is the emergence of erosion processes on the reservoir banks due to wave action on the surrounding slopes and to water level oscillation due to hydropower plant operation. Based on available technical literature, it was found that soil losses monitoring in reservoirs banks is rarely carried out and the measurement methods available are unsuitable for studies in this kind of environment. In this sense, the aim of this work is to propose an appropriate methodology for monitoring erosion processes in banks of reservoirs of hydroelectric plants, considering the lake dynamics. The proposed methodology consists of three stages, including initial planning, topographic monitoring and data analysis. In the first step is conducted a technical survey of recognition of the reservoir to be studied. The information collected is then analysed during the office planning. The second step consists in logistics planning, followed by the activities of field installation of topographical sections related to the monitoring of the stretches with erosion. In this activity are used topographical equipment (RTK System and/or total station) for collecting topographical points on the target site. The third step consists in processing topographic data obtained in the previous step and in the analysis of the resulting topographic profiles (topographical sections analysis) in the office. The methodology foresees the implementation of successive monitoring campaigns in the same location, so that the soil loss observed between successive topographic profiles can be measured. The practical application of the methodology occurred in the reservoir of Itá Hydroelectric Power Plant, located on the Uruguay River, southern Brazil. The first two monitoring campaigns were performed in January and December 2018. For the practical validation of the methodology were considered only four locations. After 11 months of first monitoring campaign, was found minimum and maximum loss of 0.111 m³ (S139) and 0.526 m³ (S141) of soil per linear metre of shoreline, respectively. The amount of eroded soil in all four sites was estimated in 70.457 m³ over 205 meters of monitored bank. Therefore, the proposed monitoring methodology presents sensitivity to detect soil losses between topographic profiles resulting from successive campaigns and is suitable for monitoring banks of large water reservoirs.